Solanum altoserranum (Solanaceae): a new species endemic from high-altitude grasslands of North-western Argentina - Bulacio, Eva; Arana, Marcelo D. (Phytotaxa, 2026)
Solanum altoserranum, a new species restricted to the high-altitude grasslands of the Calilegua and Santa Ana mountain ranges, Sub-Andean mountain system, from North-western Argentina in the altitudinal range that oscillates between 2600 and 3600 m a.s.l., is described and illustrated. The new taxon is characterized by having erect stems warty from prominent leaf bases and uniseriate, simple, eglandular, antrorse-appressed trichomes, purplish-green petioles up to 1 cm long., simple leaves with elliptic to oblong, patent, shiny lamina, purple on the abaxial surface, with notable venation that gives it a bullate appearance, apparently lateral inflorescences with 10–20 flowers, articulated pedicels, deflexed, 0.7–1 cm long, campanulate corolla, greenish-white at the base and lilac distally. Photographs, distribution information, conservation status assessment, and comparisons with similar species are also provided.